2016
DOI: 10.1007/s11442-016-1277-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in inland lakes on the Tibetan Plateau over the past 40 years

Abstract: Inland lakes and alpine glaciers are important water resources on the Tibetan Plateau. Understanding their variation is crucial for accurate evaluation and prediction of changes in water supply and for retrieval and analysis of climatic information. Data from previous research on 35 alpine lakes on the Tibetan Plateau were used to investigate changes in lake water level and area. In terms of temporal changes, the area of the 35 alpine lakes could be divided into five groups: rising, falling-rising, rising-fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 45 publications
(44 reference statements)
3
17
0
Order By: Relevance
“…Systematically monitoring lake areas therefore supports estimates of the rates of change. Our comparative analysis confirms previous findings that have reported that expanding lakes are not spread uniformly across the Tibetan Plateau [6,19,21], but are instead focused in the northeastern part of the Plateau. Compared to the distribution of glaciers (Figure 1), we found that lakes grew by the smallest amount where glaciers in the Himalayan Mountains Range are most numerous.…”
Section: Discussionsupporting
confidence: 91%
“…Systematically monitoring lake areas therefore supports estimates of the rates of change. Our comparative analysis confirms previous findings that have reported that expanding lakes are not spread uniformly across the Tibetan Plateau [6,19,21], but are instead focused in the northeastern part of the Plateau. Compared to the distribution of glaciers (Figure 1), we found that lakes grew by the smallest amount where glaciers in the Himalayan Mountains Range are most numerous.…”
Section: Discussionsupporting
confidence: 91%
“…Because the environment on the Tibetan Plateau is pristine, lakes on this remote plateau are vulnerable to the effects of anthropogenic activities. Thus, lakes on the Tibetan Plateau are considered to be sensitive indicators of global climate change (Fang et al, ; Pan & Li, ). Due to climate change, the ice‐free period for lakes on the Tibetan Plateau will become longer (Song et al, ), and the surface areas of these lakes will become more variable (Fang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The Tibetan Plateau (TP), serves as the "water tower" of Asian countries, accommodating 1055 alpine lakes with a total lake area equals to 41,831.7 km 2 [1]. It also hosts approximately 36,000 glaciers spread across the northern (Tianshan ranges), central (Tanggula mountain), and southern (Himalaya ranges) parts of the region.…”
Section: Introductionmentioning
confidence: 99%